Tipe Huruf Prasasti Masjid Girilaya - Samrotul Ilmi Albiladiyah (Berkala Arkeologi, 1994)
Girilaya, one of 16 hamlets in Wukirsari Village, Imogiri District. On the Girilaya hill there is an ancient tomb mosque. The construction of the tomb on the Girilaya hill was initiated by Sultan Agung. Under the tomb, there is an ancient mosque. In the mosque, near the pulpit, there is a short inscription written on a piece of white stone measuring 40 x 41 cm, lying between the pulpit and the wall. The Girilaya mosque inscription, which is written in New Javanese letters and languages, has its own variation of the type of letters but still shows the versatility of some of the letters. Based on the existing inscriptions, the Girilaya Mosque was built not in the same era as the Girilaya tomb, but was built during Sultan Hamengkubuwono I.